BTS MAGIC SHOP SONG AS A SELF HEALING MESSAGE MEDIA FOR HEALTH COMMUNICATION - Dini Marlinda; Nina Yuliana (Ravine Publisher, 2023)
BTS fans listen to the song Magic Shop to improve their mood, as a stress reliever, to reduce depression, to reduce pressure, or as a medium for self-healing. In the song Magic Shop, BTS conveys a message through its lyrics about mental health. BTS also invites its fans to show the best in their lives. This research aims to explain the meaning of the song Magic Shop BTS from the communicator aspect through works that stimulate young people to maintain mental health and behave more positively. This research used a constructivist paradigm a qualitative approach by applying the phenomenological method and carrying out observations and literature reviews. The data collection technique was carried out by in-depth interviews. This research refers to the SOR communication theory from Houland et al., where the communicator can provide a stimulus to the organism through his messages to change or adjust its behavior. The research results showed that Magic Shop BTS music has an influence as a means of relaxing oneself, alleviating mental health disorders such as stress, excessive anxiety, fear, and so on.